Strengthening origin compliance (2013)
Reports on the recently created international certificate of origin certification and accrediation chain which initially will concentrate on certificates of origin (COs), the most common certificates issued by Chambers of Commerce and the only ones Chambers are authorised to issue in most countries.
Keywords: CUSTOMS